Simulations of gravity wave induced turbulence using 512 PE Cray T3E - Prusa, Joseph M.; Smolarkiewicz, Piotr K.; Wyszogrodzki, Andrzej A. (Zielona Góra: Uniwersytet Zielonogórski)
A 3D nonhydrostatic, Navier-Stokes solver has been employed to simulate gravity wave induced turbulence at mesopause altitudes. This paper extends our earlier 2D study reported in the literature to three spatial dimensions while maintaining fine resolution required to capture essential physics of the wave breaking.
Keywords: nonhydrostatic gravity wave turbulence; parallel Navier-Stokes solver